Research on cognitive user pairing and cooperative sensing - Zhi-hua BAO; Shi-bing ZHANG; Xiao-ge ZHANG; Gong-an QIU (Tongxin xuebao)
Aim at the shortages of the cooperative algorithm in sensing and time slot spent,an optimal cognitive users pairing and cooperative sensing algorithm was proposed.To achieve the best sensing performance,the pairing criterion was adopted where the one with the best receive SNR was used for the sense user and the one with the second-best receive SNR was used for the relay.According to optimizing cooperation threshold,non-cooperative or cooperative mode was selected,which made time slot spent much lower but sensing ability slight decreasing.Meanwhile,a lower bound of the detection probability and the time slot spent were derived in Rayleigh flat fading channels.Numerical results show the proposed algorithm has higher detection probability and lower time slot spent than the existing one.